Sequential Treatment With Targeted and Immune Checkpoint Therapy in Patients With BRAF Positive Metastatic Melanoma: The Importance of Timing? - Grätz, Victoria; Zillikens, Detlef; Busch, Hauke; Langan, Ewan A.; Terheyden, Patrick (Frontiers in Medicine, 2019)
Background: Immune checkpoint- and targeted therapy have dramatically improved the therapeutic landscape in the management of BRAF mutation positive metastatic melanoma. However, pending the results of clinical trials, not only is it currently unclear whether immune checkpoint- or targeted therapy should be commenced up front, but the optimal time for changing treatment, specifically to prevent resistance whilst maintaining disease control, is unknown. Methods: We retrospectively identified eleven patients with BRAF V600 mutated metastatic melanoma who commenced targeted therapy between 11/2012 and 12/2017 in our center. In 5 cases the decision was made to “electively” switch to immune checkpoint therapy (elective group) following the development of a complete or partial response. In the remaining 6 cases the initial “reactive” switch was necessitated by disease progression or the development of intolerable side-effects (reactive group). Results: Overall, the elective cohort had a more favorable course in terms of overall survival (1,003 vs. 827 days), and 80% of the patients remain alive, in contrast to 17 % of the patients in the reactive group. However, it should be borne in mind that multiple switches due to disease progression were undertaken and this undoubtedly also impacted upon overall survival. Conclusion: Elective switching from targeted to immune checkpoint therapy was associated with a better outcome in terms of survival, at least in everyday clinical practice. It remains unclear whether the choice of initial therapy confers long–term survival and disease-control advantages and this should be addressed in prospective studies.